Perilaku Remaja Masjid X dalam Menyikapi Hoax di Media Sosial - Sri Mulyaningsih; Indra Wahyudi; Dewi Handayani Harahap (LPPM Universitas Proklamasi 45, 2020)
In recent 4 years, Indonesiantries to decrease the spreading of hoax news in social medias. The government has been trying various measures for instances: holding information session for public, setting some sign boards in intersections with notes like '' FIGHT FOR HOAX